Fault Identification in Power Transformers Using Dissolve Gas Analysis and Support Vector Machine - Illias H.A.; Kai Choon C.; Liang W.Z.; Mokhlis H.; Ariffin A.M.; Fairouz Mohd Yousof M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Neural networks; Power transformers; Support vector machines; Artificial intelligence techniques; Cost of maintenance; Dissolved gas analyses (DGA); Fault identifications; Life span; Training and testing; Transformer faults; Dielectric materials